2008
DOI: 10.1097/01.ogx.0000327773.92671.ad
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Prevention of Postpartum Perineal Wound Complications: A Randomized Controlled Trial

Abstract: Overt diabetes mellitus during pregnancy carries a significantly increased risk of adverse perinatal outcomes, but whether this is also true of less severe maternal hyperglycemia, or "gestational diabetes," remains uncertain. The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study was planned to clarify the risk, if any, associated with less marked maternal glucose intolerance than is associated with overt diabetes. A standard oral glucose tolerance test using a 75-g dose of glucose was carried out at 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 0 publications
2
46
0
4
Order By: Relevance
“…These complications have been found to be more common after third-or fourth-degree lacerations or midline episiotomies, or in patients with endometritis. 16 However, most of these postpartum complications occur within the first two weeks, and very few women are comfortable enough to have sex until the perineum is healed.…”
Section: Sex In the Postpartum Periodmentioning
confidence: 99%
“…These complications have been found to be more common after third-or fourth-degree lacerations or midline episiotomies, or in patients with endometritis. 16 However, most of these postpartum complications occur within the first two weeks, and very few women are comfortable enough to have sex until the perineum is healed.…”
Section: Sex In the Postpartum Periodmentioning
confidence: 99%
“…39 Limiting episiotomy to feto-maternal indications, recognition and proper closure of third and fourth degree tears, and the addition of prophylactic antibiotics in these tears have been recommended to reduce the rates of infection. 40 Teaching proper care of the perineum postpartum to maintain cleanliness of the wound is paramount to maintain the best environment for wound healing.…”
Section: Perineal/episiotomy Infectionsmentioning
confidence: 99%
“…Cefuroxim was recommended for use on a trial basis by 3 Slovak hospitals (one in combination with metronidazole) and 2 Czech hospitals, always with repeated administration. A single dose of Cefuroxim as recommended by Duggal et al [24] was not reported by any hospital. Ampicillin and first-generation cephalosporins are often resistant to bacteria present in the rectum and, hence, administration of these antibiotics as a prophylaxis is not optimal.…”
Section: Discussionmentioning
confidence: 96%
“…However, Andrews et al [20] recommend administering intravenous prophylactic antibiotics (1.5 g cefuroxim plus 500 mg metronidazole) intraoperatively and subsequently by mouth for one week for patients with obstetric anal sphincter injuries. The first randomized prospective trial comparing an intravenous single dose of a second-generation cephalosporin (Cefuroxim) perioperatively versus placebo in women with third-or fourth-degree perineal tears was published in 2008 [24]. Patients who received prophylactic antibiotics at the time of a third-or fourth-degree laceration repair had a lower rate of perineal wound complications than those who received placebo [23].…”
Section: Discussionmentioning
confidence: 98%